(untitled) (Revista Brasileira Multidisciplinar, 2026)
N-heterocyclic compounds are widely used in medicine and pharmacology due to their enormous diversity of biological activities (for example: antimicrobial, anticonvulsant, anti-inflammatory, anticancer, anthelmintic, antihistamine, antihypertensive, and antidepressant). Thus, these compounds are relevant for the synthesis of new drugs. The molecule 4-(4-Hydroxy-phenyl)-2-methyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylic acid ethyl ester was obtained using a multicomponent reaction. Its biological prospection included modulating action on phospholipases A2 and proteases, assessment of cytotoxicity and effects on processes associated with hemostasis, and antimicrobial activity. Several doses of the molecule were tested in each test, ranging from 25 to 500 mg. For antimicrobial activity, in the serial dilution test, the molecule exerted significant inhibitions for both S. aureus and P. aeruginosa. When assessed the effects on the coagulation of citrated human plasma, the molecule previously incubated with Bothrops moojeni venom (40 µg) was able to delay plasma coagulation, induced by proteases, in 14 and 13.66 seconds (p<0.05) at doses of 125 and 100 mg, respectively. Furthermore, the synthesized compound previously incubated with plasma, with the subsequent addition of venom, was able to prolong the clotting time in all evaluated doses (p<0.05). B. moojeni venom had its thrombolytic activity reduced to 73, 88, and 82% (p<0.05) when incubated with the compound at doses of 125, 100, and 50 mg, respectively. The phospholipase activity induced by the venom was significantly reduced after incubation of the venom with the compound at the highest dose (125 mg). In addition, a protective effect on human erythrocytes was exerted by the compound at all doses evaluated against B. moojeni venom (20 µg). Thus, in this manuscript, a relatively simple multicomponent reaction protocol (satisfactory yield, low cost, and ecologically adequate) was presented, in which the resulting molecule presented several biological activities that can be better explored for future applications in the context of human health.